BUDAYA ORGANISASI, INSENTIF, KEPUASAN KERJA, DAN KINERJA KARYAWAN PADA PT AVRIST ASSURANCE - Iha Haryani Hatta; Widarto Rachbini (Jurnal Manajemen., 2015)
The purpose of this study was to determine the effect of organizational culture and incentive on job satisfaction and employees’ performance. The study was conducted in PT Avrist Assurance, using 211 employees as respondents. The sampling technique in this research is simple random. The analysis was performed with Structural Equation Model (SEM) using Lisrel 8.5. The study found that organizational culture and incentives significantly affect job satisfaction and employees’ performance. Moreover, job satisfaction significantly affect employees’ performance. The total effect of organizational culture on Job Satisfaction and employee performance is more dominant than the total effect of incentives on Job Satisfaction and employee performance.